(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The activities offered by beekeeping (bee products, api-therapy, beehive air, bee museums, production activities, historical beekeeping activities, pictures, and others) are aimed at attracting beekeepers and people who want to earn and increase national income. The purpose of the study: to investigate the possibilities of using the beekeeping industry in the national economy of Latvia. Research object: Latvian agricultural sector - Beekeeping. Within the framework of the research, the literature of different countries related to beekeeping, data collection, processing, survey and observation, processing and description of the obtained data were studied. The beekeeping industry could play an important role in promoting the development of the national economy, because the export of honey in Latvia is already much higher than the import, which can be evaluated positively from an economic point of view, honey and beekeeping by-products are in demand. However, in order to achieve the set goal, it is important to involve the government and local governments, promoting the development of beekeeping in the regions, helping with realization opportunities. Utilizing the available potential requires high-level professionals, modernization of equipment and greater protection of the environment from pollution, all of which can be realized if the government increases informational and financial support for the beekeeping industry, because in the long term it would contribute to the economic growth of the country. ;